Approximation of Signals (Functions) by Trigonometric Polynomials in Lp-Norm. (9th April 2014) - Mittal, M. L.; Singh, Mradul Veer
Abstract : Mittal and Rhoades (1999, 2000) and Mittal et al. (2011) have initiated a study of error estimatesE n ( f ) through trigonometric-Fourier approximation (tfa) for the situations in which the summability matrixT does not have monotone rows. In this paper, the first author continues the work in the direction forT to be aN p -matrix. We extend two theorems on summability matrixN p of Deger et al. (2012) where they have extended two theorems of Chandra (2002) usingC λ -method obtained by deleting a set of rows from Cesàro matrixC 1 . Our theorems also generalize two theorems of Leindler (2005) toN p -matrix which in turn generalize the result of Chandra (2002) and Quade (1937).